Uncertainty of outcome versus reputation: empirical evidence for the First German Football Division - Dirk Czarnitzki; Georg Stadtmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper analyses the determination of match attendance in the German premier football league by applying models derived from Peel/Thomas (1992) and Janssens/Késenne (1987). Additionally we develop an improved version, where we incorporate the supporter clubs and the weather conditions as explanatory variables. While we consider this problem more or less from the consumer perspective, the information gained though this model can also serve as a management tool for football clubs: The returns are directly related to the number of tickets sold. Furthermore, the funds raised by merchandising and advertising are also closely linked to the attendance figures. Due to the limited capacity of the stadiums, some obsevations on attendance are right censored in our sample. While other authors use the ordinary least squares estimator, which produces inconsistent results when events were sold out, we take this restriction implicitly in consideration by using a Tobit model. In conclusion, we show that reputation and goodwill are more important for attendance levels than the thrill of outcome uncertainty.
Keywords: D12; C24; 330; Consumer Demand; Team Sports; Tobit Estimator; Fußballsport; Nachfrage; Sportökonomik; Risiko; Prestige; Schätzung; Deutschland